The Role of Political Competition and Government Size to Enhance Government Financial Transparency - Octa Azzani, Olivia; Fontanella, Amy; Chandra, Novrina; Afni, Zalida (International Ecsis Association, 2024)
This study aims to analyze the influence of political competition and local government size on local government financial transparency in Indonesia. This study was conducted in 362 local governments in Indonesia. Local government financial transparency was measured through the disclosure of financial information at the planning, implementation, and reporting stages carried out on the official government websites. Political competition was proxied by the percentage of regional legislative members from the party supporting the regional head compared to the total number of council members in each district or city. The findings indicate that financial transparency is positively affected by political competition. Regions with higher political competition are found to disclose more financial information through their official websites, as increased competition leads to more stringent oversight. Furthermore, it is revealed that larger local governments disclose more financial information, indicating that governments with greater assets tend to maintain better transparency due to their access to adequate resources. Additionally, the demand for transparency is higher in larger governments. This study providing empirical evidence on the positive impact of political competition and local government size on financial transparency, highlighting the role of competitive governance and resource adequacy in fostering accountability through online financial disclosures in Indonesia.